Demand and innovation: theory and evidence - Herbert Dawid; Gabriele Pellegrino; Marco Vivarelli (Global Labor Organization (GLO), 2017)
While the extant innovation literature has provided extensive evidence of the so-called "demand-pull" effect, the possible diverse impact of demand evolution on product vs process innovation activities has not been yet investigated. This paper develops a formal model predicting a larger inducing impact of past sales in fostering product rather than process innovation. This prediction is then tested through a dynamic microeconometric model, controlling for R&D persistence, sample selection, observed and unobservable individual firm effects and time and sectoral peculiarities. Results are consistent with the model and suggest that an expansionary economic policy may benefit the diffusion of new products or even the emergence of entire new sectors.
Keywords: O31; 330; technological change; R&D; demand-pull innovation; dynamic two tobit